Autofictions in Co-labouring - Diana Damian Martin; Daniela Perazzo; Nik Wakefield (Performance Philosophy, 2024)
In this co-authored text, the Dissonant Co-Labouring Key Group examines the difficulties, gaps, political slippages and entanglements of collaboration in its encounter with artistic and educational institutions. Engaging autofiction as a scholarly mode with different models of co-authorship, the Key Group move through critical engagements with working conditions, temporalities of labour and its instrumentalisation within and beyond universities and cultural ecologies. Dialoguing with a plurality of voices and registers, the text invokes adjacent and overlapping temporalities of working together, attends to different modalities of critical thought and collapses the distinction between the fictive and the real.